Umbilical keratinous cyst in a 7-year-old girl: A case report - Ghritlaharey, Rajendra K (Indian Journal of Child Health, 2024)
Keratinous cysts, the most common kind of epidermal cysts, are filled with keratin originating from the epidermis, most often from the hair follicle. Keratinous cyst is one of the most common skin lesions and occurs most commonly in the face, head, trunk, extremities, and genitals. A 7-year-old girl reported to the pediatric surgery department with a painless, small tumor arising from her umbilicus. There was no history of trauma, and it has been slowly growing for the past many years. Clinical examination revealed a 3-cm-long skin tag with three small interconnected tumors from the umbilicus. It was soft, and the parts of the tumors looked like they contained whitish material inside. Her general and other systems, including the abdominal examinations, were within the normal limits. The tumor was resected through a sub-umbilical skin incision. She made an uninterrupted recovery. The excised specimens subjected to histology were reported as superficial keratinous cysts. Keratinous cysts are one of the most common benign skin lesions, but not the most common, at the umbilicus. Clinicians need to be aware of such pathology during the evaluation of the umbilical swellings and tumors, especially in children.